Body experience in the east-slavonic culture tradition - Ye. I. Kirilenko (Бюллетень сибирской медицины, 2006)
In the modern science, the body is an object of interest not only to the natural science and medicine, but also the humanities. Of special interest, in particular, for the medical discourse, is the ethnic body experience. The paper reveals features of the body experience in the east-slavonic culture from the analysis of the mythological tradition. This experience is characterized by the pronounced interest and ambivalent attitude to the body’s life, natural body standards; and emotional intensity. The experience of the social body is of highest priority in the culture.